2014
DOI: 10.1002/eji.201343995
|View full text |Cite
|
Sign up to set email alerts
|

CCR4 and CXCR3 play different roles in the migration of T cells to inflammation in skin, arthritic joints, and lymph nodes

Abstract: CCR4 and CXCR3 are expressed on several T-cell subsets in inflamed tissues, yet their role in tissue-specific recruitment is unclear. We examined the contributions of CCR4 and CXCR3 to T-cell recruitment into inflamed joints in collagen-induced arthritis, antigendraining lymph nodes (LNs) and dermal inflammatory sites (poly I:C, LPS, concanavalin A, and delayed type hypersensitivity), using labeled activated T cells from CXCR3 −/− , CCR4 −/− , and WT mice. Both CXCR3 and CCR4 deficiency reduced the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…To further support these findings, we next investigated the expression of three selected chemokine receptors known to be differentially expressed by T cell subsets with distinct functions (Becattini et al, 2015) and whose alternative combined expression regulates T cell recirculation and migration to diverse homing sites (Al-Banna et al, 2014; Bromley et al, 2008; Thomas et al, 2007). Both resting MR1T and MAIT cell clones displayed high levels of CXCR3 (with the exception of the DGA4 clone only; Figure 7B), However, we observed divergent expression patterns of CCR4 and CCR6 (Figure 7B), which further suggested that MR1T cells are heterogeneous and different from MAIT cells.…”
Section: Resultsmentioning
confidence: 99%
“…To further support these findings, we next investigated the expression of three selected chemokine receptors known to be differentially expressed by T cell subsets with distinct functions (Becattini et al, 2015) and whose alternative combined expression regulates T cell recirculation and migration to diverse homing sites (Al-Banna et al, 2014; Bromley et al, 2008; Thomas et al, 2007). Both resting MR1T and MAIT cell clones displayed high levels of CXCR3 (with the exception of the DGA4 clone only; Figure 7B), However, we observed divergent expression patterns of CCR4 and CCR6 (Figure 7B), which further suggested that MR1T cells are heterogeneous and different from MAIT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Given these reports, we cannot rule out that defective CXCL10 signaling in those cells including neutrophil and fibroblast-like synoviocytes might contribute to the inhibitory results of arthritis progression seen in Cxcl10 –/– and Cxcr3 –/– mice in our study. Furthermore, it has been reported that the accumulation of T cells in inflamed lymph nodes is highly CXCR3 dependent, but not CCR4 dependent [37]. Thus, we speculated that decreased recruitment of T cells in other organs including inflamed lymph nodes, not only in the synovium, would be observed in Cxcl10 –/– and Cxcr3 –/– mice; however, this hypothesis remains to be elucidated.…”
Section: Discussionmentioning
confidence: 84%
“…CAIA is reported to be induced by infiltration of neutrophils and macrophages, which are the main effector cells in CAIA, into the inflamed joints [20, 21, 36]. Al-Banna et al [37] showed that the accumulation of T cells in inflamed lymph nodes is highly CXCR3 dependent and that CXCR3 deficiency reduces the development of arthritis in a CIA model. In addition, Mohan and Issekutz [17] showed that blockade of CXCR3 inhibits T-cell and neutrophil recruitment to inflamed joints and decreases the severity of adjuvant arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the recruitment of Tregs is often associated with CCR4 and CCR5 chemokine receptors. CCR4 can mediate migration of Tregs to airway and to inflammation in skin, arthritic joints, and lymph nodes (34). CCR5 signaling suppresses inflammation and reduces adverse remodeling of the infarcted heart-mediating recruitment of Tregs (35).…”
Section: Discussionmentioning
confidence: 99%